2018
DOI: 10.1016/j.dib.2018.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Data of heavy metals in soil and groundwater at Kiwi gardens of Amlash in Guilan Province, Iran

Abstract: Data on this paper describe the concentrations of arsenic, cadmium, copper, nickel, lead and zinc in the surface soils and groundwater's of Kiwi gardens and its relation to chemical fertilizers in Amlash city, Guilan Province, in Iran. The results of this study showed that the average concentration of heavy metals in groundwater and soils of the studied areas was less than the national standards of Iran for irrigation water, Dutch MPA for soils (except Cu and Ni) and Canadian MAC for inorganic fertilizers. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the study of Naghipour et al (2018) on trace element contents of surface soils and groundwaters in Guilan Province, Iran, and their relation to chemical fertilizer addition, it was revealed that fertilization increased trace element (Cd, Cu, Ni, Pb, and Zn) contents in soil and groundwater samples. Naghipour et al (2018) stated that significant increase of trace element contents of soils and groundwaters following fertilizing soils reveals that chemical fertilizers have a crucial role in elevation of trace element contents in soils and groundwaters.…”
Section: Trace Element Contents In Soilsmentioning
confidence: 99%
“…In the study of Naghipour et al (2018) on trace element contents of surface soils and groundwaters in Guilan Province, Iran, and their relation to chemical fertilizer addition, it was revealed that fertilization increased trace element (Cd, Cu, Ni, Pb, and Zn) contents in soil and groundwater samples. Naghipour et al (2018) stated that significant increase of trace element contents of soils and groundwaters following fertilizing soils reveals that chemical fertilizers have a crucial role in elevation of trace element contents in soils and groundwaters.…”
Section: Trace Element Contents In Soilsmentioning
confidence: 99%
“…Environmental pollution like drinking water and soil pollution by heavy metals is one of the most important issues in the world due to no-biodegradability of the metals and their impact on living organisms in concentration greater than thresholds (Naghipour et al 2018).…”
Section: Introductionmentioning
confidence: 99%